ลักษณะความเป็นอมตะของเพลงสุนทราภรณ์ - พิชญ์สินี บำรุงนคร (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
The objective of this research was to understand the characteristics of Suntharaporn songs and to determine the factors which contributed to making Suntharaporn songs immortal. The data collection instruments were as follows: content analysis, focus group, and in-depth interview. The researcher used these instruments to understand the characteristics of Suntharaporn songs and the last two instruments to indicate the factors which contributed to making Suntharaporn songs immortal. The researcher analysed the content of the songs, and the data from the audience, the people who were involved in creating the songs, expert musicians, expert singers and radio producers. The results of the analysis show the characteristics of Suntharaporn songs. The content of the songs must consist of the relevance between the lyrics and the melody and be meaningful. It must relate to prosody, and literary style. The melody and the rhythm assign meaning to the songs and must be relevant to the emotions found in those kinds of melodies and rhythms. The content must be based on popular music. Moreover, the aesthetics which comprises melodiousness, being familiar to the perception of the audience, as well as excellence is important. The main factors which determine its immortality are the media, and reproduction. The singers must sing beautifully and can express the emotions of the songs, the correct use of polite gestures on stage and their amount of practice. The musicians must specialise in music. They must have the gift, and experience in music, including an ability to work with other artists in Suntharaporn band. The lyric writers must be good in Thai, possess experience in writing lyrics and be accustomed to the notes. The composers and the arrangers must specialise in writing and arranging music and have thought, imagination and an ability to work together. The music trainers should specialise in music and be able to work with the singers and the musicians. The research findings imply that the immortality involves the valuable work which artists leave for audiences. Furthermore, it concerns time. The work must last long and be memorable for at least 2-3 generations of audiences.